The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24076049
|View full text |Cite
|
Sign up to set email alerts
|

The MdmiR156n Regulates Drought Tolerance and Flavonoid Synthesis in Apple Calli and Arabidopsis

Abstract: Drought is the major abiotic stress that limits apple productivity and quality. To date, many important and divergent regulatory functions of miR156/SBP genes in plant growth and development have been well understood. However, little is known about the role of apple miR156 in response to abiotic stress. To better understand the functions of MdmiR156 in abiotic stress tolerance, we constructed the overexpression (OE) and short tandem target mimic (STTM) vector of MdmiR156n and performed its functional analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…In the present study, we successfully knocked down csn-miR156f-2-5p and found that tea plants with csn-miR156f-2-5p knocked down might be more sensitive to drought ( Figure 6 ). This is consistent with previous findings showing that plants with miR156silence are more susceptible to drought stress than the corresponding WT with regard to Arabidopsis and apples [ 48 , 49 ].MicroRNAs function by cleaving the corresponding mRNA or inhibiting translation to regulate the expression of their target genes [ 12 ]. SPLs are genes with crucial roles in plants’ response to abiotic stress and their development, and they are the main target genes of miR156s [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we successfully knocked down csn-miR156f-2-5p and found that tea plants with csn-miR156f-2-5p knocked down might be more sensitive to drought ( Figure 6 ). This is consistent with previous findings showing that plants with miR156silence are more susceptible to drought stress than the corresponding WT with regard to Arabidopsis and apples [ 48 , 49 ].MicroRNAs function by cleaving the corresponding mRNA or inhibiting translation to regulate the expression of their target genes [ 12 ]. SPLs are genes with crucial roles in plants’ response to abiotic stress and their development, and they are the main target genes of miR156s [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…The higher level of flavonoids probably contribute to the cold tolerance in inbred line N28 waxy corn . Overexpression of MdmiR156n promoted the accumulation of flavonoids and reduced the accumulation of ROS under drought conditions in transgenic apple calli and Arabidopsis thaliana plants . The ectopic expression of flavonoids synthetase genes from Apocynum venetum including AvF3H , AvF3′H , and AvFLS notably increased the salt tolerance but reduced the ROS content in transgenic Arabidopsis, suggesting that the flavonoids improve the salt tolerance by increasing the ROS scavenging capacity in plants .…”
Section: Introductionmentioning
confidence: 98%
“…13 Overexpression of MdmiR156n promoted the accumulation of flavonoids and reduced the accumulation of ROS under drought conditions in transgenic apple calli and Arabidopsis thaliana plants. 14 The ectopic expression of flavonoids synthetase genes from Apocynum venetum including AvF3H, AvF3′H, and AvFLS notably increased the salt tolerance but reduced the ROS content in transgenic Arabidopsis, suggesting that the flavonoids improve the salt tolerance by increasing the ROS scavenging capacity in plants. 15 ABA induced the accumulation of flavonoids, including anthocyanin, naringin, quercetin, isorhamnetin, kaempferol, and catechin, to improve the antioxidant capacity of Nitraria tangutorum Bobr.…”
Section: ■ Introductionmentioning
confidence: 99%